Instruction Increases Canadian Students' Preference for and Use of Lateral Reading Strategies to Fact-Check Online Information - Jessica E. Brodsky; Patricia J. Brooks; Dimitri Pavlounis; Jessica Leigh Johnston (SAGE Publishing, 2023)
Canadian middle and high school students (N = 2,278) completed a "CTRL-F" curriculum teaching them how to evaluate online information by reading laterally to investigate sources, check claims, and trace information to original contexts. A subset of CTRL-F students (N = 316) were in classes with teacher-matched control groups (N = 287). Some CTRL-F students (N = 994) completed a delayed posttest. At pretest, students indicated preference for some lateral reading strategies, but preference rarely translated into use. Following instruction, CTRL-F students showed greater preference for and use of lateral reading than controls and greater alignment between preference and use. The curriculum's impact varied by demographic factors but not by differences in implementation. Gains were maintained from posttest to delayed posttest. Direct instruction and practice in lateral reading appear to strengthen connections between students' preferences and utilization of these strategies to evaluate online content relevant to academic and personal life.